2017
DOI: 10.21548/38-2-1391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Torulaspora delbrueckii Yeast Treatment on Flavanols and Phenolic Acids of Chenin blanc Wines

Abstract: The non-Saccharomyces yeast Torulaspora delbrueckii contributes positively to the sensory properties of wines by affecting aroma and flavour due to changes in alcohols, esters, fatty acids and lactone levels. One of the less-studied aspects of T. delbrueckii is its effect on phenolic compounds relating to sensory attributes. An HPLC-DAD technique was used for the quantification of phenolic compounds in Chenin blanc wines made with S. cerevisiae and two T. delbrueckii yeasts over three vintages. Chemical and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
16
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 27 publications
(26 reference statements)
9
16
3
Order By: Relevance
“…Wines produced from the T. delbrueckii strain M2/1 treatment also had high scores and were often judged to be significantly better than the other wines in terms of the "fruity and fermentation" character and "general quality" (Table 2). These results correspond to the findings of previous studies, which found that non-Saccharomyces yeasts contributed to mouthfeel and improved the quality of wines (Ciani & Picciotti, 1995;Ciani & Maccarelli, 1998;Minnaar et al, 2015;Ngqumba et al, 2017). The results also support the findings of Albertin et al (2017) on the already mentioned link between non-Saccharomyces yeasts, the duration of the S. cerevisiae lag phase and the wine's fruitiness and complexity.…”
Section: Small-scale Vinification: Chenin Blancsupporting
confidence: 91%
See 1 more Smart Citation
“…Wines produced from the T. delbrueckii strain M2/1 treatment also had high scores and were often judged to be significantly better than the other wines in terms of the "fruity and fermentation" character and "general quality" (Table 2). These results correspond to the findings of previous studies, which found that non-Saccharomyces yeasts contributed to mouthfeel and improved the quality of wines (Ciani & Picciotti, 1995;Ciani & Maccarelli, 1998;Minnaar et al, 2015;Ngqumba et al, 2017). The results also support the findings of Albertin et al (2017) on the already mentioned link between non-Saccharomyces yeasts, the duration of the S. cerevisiae lag phase and the wine's fruitiness and complexity.…”
Section: Small-scale Vinification: Chenin Blancsupporting
confidence: 91%
“…Metabolic, chemical and sensory profile studies of non-Saccharomyces yeast fermentations have shown that T. delbrueckii species in particular make a positive contribution toward the flavour of alcoholic beverages (Ciani & Picciotti, 1995;Ciani & Maccarelli, 1998;Jolly et al, 2003a;Van Breda et al, 2013;Belda et al, 2015;Loira et al, 2015;Renault et al, 2015;Chen & Liu, 2016;Renault et al, 2016;Ngqumba et al, 2017). This was further demonstrated in a study conducted by Hernández-Orte et al (2008), in which wines produced with T. delbrueckii had high concentrations of aliphatic lactones and ethyl dihydrocinnamate, imparting sensory notes such as "dried fruit" and "coconut" to the wine.…”
Section: Introductionmentioning
confidence: 93%
“…On another note, T. delbrueckii has been also shown to modulate other phenolic compounds in wine. In this respect, Ngqumba et al (2017) observed that the influence of T. delbrueckii on the phenolic composition of wine (i.e., flavonols and phenolic acids) of cv. Chenin blanc depended on the specific strain.…”
Section: Discussionmentioning
confidence: 98%
“…Fermentations involving M. pulcherrima co-inoculated with lactic bacteria showed higher final concentrations of p -coumaric acid than the S. cerevisiae controls by about 25% [ 69 ]. Other non- Saccharomyces species also produce wines with higher p -coumaric acid contents [ 70 , 71 , 72 , 73 ]. This explains the higher concentrations of cumarilated anthocyanins.…”
Section: Fermentation Parametersmentioning
confidence: 99%